Firm-specific Training: Consequences for Job Mobility - Rudolf Winter-Ebmer; Josef Zweimüller (Institute for the Study of Labor (IZA), 2000)
This paper analyzes the impact of formal training on worker mobility. Using data from the Swiss Labor Force Survey, we find that on-the-job search activities and, to a smaller extent, actual job separations are significantly affected by both employer-provided and general training. Moreover, while the separation probability of searching workers is strongly affected by previous firmprovided training, no such effect shows up for non-searchers. This is consistent with the hypothesis that workers bear most of the cost of specific training.
Keywords: J63; J24; 330; Firm-specific training; on-the-job-search; turnover; Betriebliche Bildungsarbeit; Berufsbegleitende Ausbildung; Arbeitsmobilität; Schweiz